On the Essence of the Concept of “Aspectual Situation” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the scholarly investigation of the concept of the “aspectual situation,” which is widely used in the field of aspectology. The author analyzes the views of international linguists on this issue and synthesizes their scientific approaches. The results of the study contribute to a deeper understanding of the essence of this concept and broaden the possibilities of its application in linguistics.